Numerical investigation of the polymer melt flow in injection molding by using ILU preconditioned GMRES - Türk, U.; Ecder, A. (Mathematical Modelling and Analysis, 1999)
The implementation of a modern preconditioned Newton‐Krylov solvers to the polymer melt flow in injection molding is the main focus of this paper. The viscoelastic and non‐isothermal characteristics of the transient polymer flow is simulated numerically and the highly non‐linear problem solved. This non‐linear behavior results from the combination of the dominant convective terms and the dependence of the polymer viscosity to the changing temperature and the shear rate. The governing non‐Newtonian fluid flow and energy equations with appropriate approximations are discretized by finite differencing. Elliptic Grid Generation technique is used to map physical domain to computational domain. The resulting non‐linear system is solved by using Newton’s method. GMRES, one of the Krylov subspace methods, used as an iterative algorithm in order to solve the linear system at each non‐linear step. Incomplete LU preconditioner is used for better convergence. Numerical solution of polymer flow is presented to demonstrate that these methods are efficient and robust for solving such flow problems. Polimerinio lydinio tekėjimo skaitinė analizė panaudojant GMRES metodą su ilu sąlygotumą gerinančia matrica Santrauka. Šiame darbe nagrinėjamas šiuolaikinių Niutono‐Krylovo metodų efektyvumas, kai jais sprendžiame polimerinio lydinio tekėjimo uždavinį. Uždavinys yra stipriai netiesinis, tai sąlygoja vyraujančių konvekcinių narių sąveika ir koeficientų priklausomybė nuo temperatūros. Uždavinys aproksimuojamas baigtinių skirtumų schema. Panaudojant elipsinį tinklo generatorių fizinė skaičiavimo sritis yra atvaizduojama į skaičiavimo sritį. Gautoji netiesinių lygčių sistema sprendžiama Niutono metodu. Kiekviename iteraciniame žingsnyje tiesinių lygčių sistema sprendžiama GMRES metodu, kuris modifikuojamas nepilnos LU faktoriza‐cijos neišreikštiniu operatoriumi. Pateiktieji skaičiavimo eksperimento rezultatai iliustruoja algoritmų efektyvumą ir universalumą. First Published Online: 14 Oct 2010